The Hip and Pelvis in Sports Medicine and Primary Care - Seidenberg MD, FAAFP, FACSM, RMSK, Peter H.; Bowen MD, FAAPMR, CAQSM, RMSK, CSCS, Jimmy D.; King MD, David J. (Springer International Publishing : Imprint: Springer, 2017)
Now in a revised and updated second edition, this practical guide remains an invaluable resource for improving the management of hip and pelvis injuries and presents a spectrum of treatment options for children, adolescents, adults and special populations. Opening with valuable clinical pearls for each topic, differential diagnosis is emphasized throughout the chapters, and evidence-based guidelines and sport-specific considerations aid the reader with injury evaluation and care. From fundamentals-including epidemiology, history and physical examination, imaging and gait assessment-to functional therapeutic interventions, injection techniques, taping and bracing, and both surgical and non-surgical interventions, The Hip and Pelvis in Sports Medicine and Primary Care, Second Edition is ideal for sports medicine physicians, primary care physicians, physical therapists and athletic trainers alike.
Keywords: Medicine.; Orthopedics.; Primary care (Medicine).; Sports medicine.; elektronické knihy; electronic books